Mangrove (Bruguiera gymnorrhiza) leaves potential as colouring agent on cotton, rayon, and sateen fabrics - Anggryani, Cucuk Trisnawati; Munir, Misbakhul; Maisaroh, Dian Sari (Journal of Marine Resources and Coastal Management, 2021)
This study aims to find the value of the fastness test of the natural dye of mangrove leaves (Bruguiera gymnorrhiza). This research was conducted in June-November 2020. This research used descriptive and experimental methods. The samples used were cotton, rayon, and sateen fabrics. The experimental results showed the addition of fixator tunjung (FeSO4) capable of binding dye mangrove leaves Bruguiera gymnorrhiza that give color to the fabric fibers. The result of the coloring is brownish yellow. The results of the color fastness value in hot water are influenced by the difference in ΔE (colorfastness), cotton fabrics have a range of values ​​between the medium category (5.1-5.94), the medium-large category rayon cloth (5.09-9.06 ), medium category sateen (3.65-4.35). The results of the color fastness value in cold water are influenced by the difference in ΔE (colorfastness), cotton fabrics have a range of values ​​between the small and medium categories (1.96-3.68), rayon fabrics in the small category (2.83-3.9 ), the small category of sateen fabrics (1.54-2.76).